KETERLIBATAN TNI DALAM PENANGANAN AHMADIYAH DI JAWA BARAT - Ryllian Chandra (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2015)
One of the tasks of TNI is conducting Military Operations Other Than War. One forms of Military Operation Other Than War is Assistance to Local Governments. TNI involvement in the handling of Ahmadiyah in West Java was impact of that policy. As a result of those involvement was military re- entry into a political issue, then also raises human rights violations in its implementation.